Exogenous Interleukin-37 Alleviates Hepatitis with Reduced Dendritic Cells and Induced Regulatory T Cells in Acute Murine Cytomegalovirus Infection - Yufei Ruan; Zhengwang Wen; Ke Chen; Jianan Xi; Bo Wu; Zhiyong Xu; Minzhi Jiang; Junling Zhang; Yiping Chen; Qi Liu (Journal of Immunology Research)
Human cytomegalovirus (HCMV) infection is globally distributed, and the liver is one of the major targeting organs. So far, the mechanisms for cell and organ damage have not fully been elucidated and the treatments for the infection are mainly at symptoms. IL-37 has shown a protective role in certain inflammatory diseases. In the present study, potential protective effect of exogenous IL-37 on murine cytomegalovirus- (MCMV-) infected hepatitis was evaluated through analyses of serum transaminases, the liver histopathology and cytokine expression, and functional state of dendritic cells (DCs) and regulatory T cells (Tregs). These analyses showed a significant decrease in serum transaminase levels and a lower Ishak histopathologic score at the early stage of MCMV-infected mice with exogenous IL-37 pretreatment. The frequencies of MHC-Ⅱ, CD40, CD80, and CD86 positive DCs in the liver and spleen were decreased significantly at 7 days postinfection (dpi) in MCMV-infected mice with IL-37 pretreatment when compared with those without the pretreatment, while the total number of DCs in the liver was reduced in IL-37-pretreated mice. The induction of Tregs in the spleen was enhanced at dpi 3 with IL-37 pretreatment in MCMV-infected mice. The mRNA expression levels of cytokines in the liver were decreased significantly (IL-1β, IL-6, IL-10, IL-4) or to some extent (TGF-β and TNF-α). The present study suggested that exogenous IL-37 can alleviate MCMV-infected hepatitis, likely through reduced DCs and induced Tregs with a weaker cytokine storm, demonstrating its potential value in clinical management for HCMV-infected hepatitis.